A retrospective study of clinical and histopathological spectrum of genital lichen sclerosus in a tertiary care center - Sunanda A Mahajan; Shubhangi H Mahajan; Uday S Khopkar; Vidya D Kharkar (Wolters Kluwer Medknow Publications, 2019)
Background: Genital lichen sclerosus (LS) is a chronic, autoimmune, inflammatory dermatosis of genitalia more common in females than males. Diagnosis of early genital LS is difficult clinically; hence, histopathology may help to confirm the diagnosis. Aims: The aim of this retrospective study was to elucidate the epidemiology of genital LS and to correlate the clinical and histopathological features of genital LS. Methods: Records of 30 clinically diagnosed patients of genital LS with 27 biopsies included in the study. Clinical data from the records reviewed. Histopathological parameters noted and accordingly cases classified into early, evolved, and mature LS and correlated with clinical features. Results: Genital LS was more common in females with early age of onset. Adult patients had longer duration of disease. Pruritus was the most common symptom and females were more symptomatic. Hypothyroidism was the associated autoimmune disease in two cases. Out of thirty patients, six had genital with perianal involvement and two had genital with the extragenital disease. Phimosis was the most common complication in males, while introital stenosis was the most common in females. Lymphohistiocytic infiltrate was the most common histopathological finding followed by hyperkeratosis, dilated blood vessels and lymphatics, and collagen homogenization. Duration, symptoms, and clinical features were found to be independent of the histopathology findings. Limitations: It is a retrospective study with limited patient information. Association of genital LS with other autoimmune diseases cannot be commented as required investigations were not done. Our data are cross-sectional without follow-up, hence the disease course and treatment outcome could not be commented. Conclusions: Genital LS is prevalent in adult females but childhood occurrence is uncommon. Perianal affection occurs almost exclusively in women with genital LS. Understanding variations in histopathologic features is vital to appropriate clinicopathologic correlation. Long-term follow-up is recommended.